2017
DOI: 10.1111/gcb.13737
|View full text |Cite
|
Sign up to set email alerts
|

Higher yields and lower methane emissions with new rice cultivars

Abstract: Breeding high-yielding rice cultivars through increasing biomass is a key strategy to meet rising global food demands. Yet, increasing rice growth can stimulate methane (CH ) emissions, exacerbating global climate change, as rice cultivation is a major source of this powerful greenhouse gas. Here, we show in a series of experiments that high-yielding rice cultivars actually reduce CH emissions from typical paddy soils. Averaged across 33 rice cultivars, a biomass increase of 10% resulted in a 10.3% decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 59 publications
3
70
0
1
Order By: Relevance
“…Elevated CO 2 increased rice root growth and plant biomass in all three experiments (Tables S2-S4), confirming numerous previous studies (van Groenigen et al, 2013;Lou et al, 2008). Larger rice plants stimulate O 2 transport into soils (Jiang et al, 2017;Ma, Qiu, & Lu, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Elevated CO 2 increased rice root growth and plant biomass in all three experiments (Tables S2-S4), confirming numerous previous studies (van Groenigen et al, 2013;Lou et al, 2008). Larger rice plants stimulate O 2 transport into soils (Jiang et al, 2017;Ma, Qiu, & Lu, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…This mechanism is particularly important in soils with straw addition, where soil CH 4 concentrations are relatively high (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of this linear mixed model is that it can handle many variables together, and makes use of the large number of unsystematic field measurements (Jørgensen and Fath, 2011;Yan et al, 2005a). The results of our previous modeling analysis (Yan et al, 2005a) have been adopted by the 2006 IPCC guidelines as the inventory-based (i.e., Tier 1 and 2 methods) approaches in which a baseline default EF and various scaling factors were estimated (Lasco et al, 2006).…”
Section: The Advantages Of the Statistical Modelmentioning
confidence: 99%
“…Previous studies have shown that CH 4 emissions from rice fields have been influenced by water management (Wang et al, 2012;Zou et al, 2005), nitrogen (N) fertilizer use (Banger et al, 2012), organic input (Feng et al, 2013;Wang et al, 2013) and rice varieties (Jiang et al, 2017;Watanabe et al, 1995). Using a statistical analysis of a large data set of field measurements, Yan et al (2005a) revealed that the primary factors that control CH 4 emissions were organic amendments, the agroecological zone, water regimes during and before the rice-growing season and soil properties.…”
Section: Introductionmentioning
confidence: 99%
“…Changes to rice cultivation are farther along, including temporary drainage regimes and cultivar selection. A recent study has shown that higher‐yielding cultivars of rice can increase yield ~10% while reducing CH 4 emissions by a similar amount, potentially through increased oxygen transport through roots to the soil (Jiang et al, ). Within the fossil fuel sector, opportunities for mitigating emissions are already being exploited.…”
Section: The Role Of Atmospheric Ch4 In Achieving Global Climate Targetsmentioning
confidence: 99%